Report on business attachment with Cold Storage Retail. - Swee, Joanna Ming Li. (2009)
This report is aimed at providing the students at the School of Accountancy and Business with an insight into the business training experience achieved during the Business Attachment Programme in second year. In this case, the organisation attached to is Cold Storage Retail - Supermarket (Jelita). The purpose is to provide a summary of the experience and highlighting on particular aspects of the training that was found to be most stimulating.